Growth differentiation factor‐15 is not modified by sacubitril/valsartan and is an independent marker of risk in patients with heart failure and reduced ejection fraction: the PARADIGM‐HF trial. (11th September 2018) - Bouabdallaoui, Nadia; Claggett, Brian; Zile, Michael R.; McMurray, John J.V.; O'Meara, Eileen; Packer, Milton; Prescott, Margarett F.; Swedberg, Karl; Solomon, Scott D.; Rouleau, Jean L.; ,
Abstract : Aims: Growth differentiation factor‐15 (GDF‐15) is associated with adverse prognosis in cardiovascular (CV) and non‐CV diseases. We evaluated the association of GDF‐15 with CV and non‐CV outcomes in the PARADIGM‐HF trial. Methods and results: In 1935 patients with heart failure and reduced ejection fraction (HFrEF) in PARADIGM‐HF, median GDF‐15 values were elevated and similar in sacubitril/valsartan and enalapril patients (1626 ng/L and 1690 ng/L, respectively). Diabetes, age, creatinine, high‐sensitive troponin T, N‐terminal pro‐B‐type natriuretic peptide, and New York Heart Association class III/IV were most strongly associated with elevated GDF‐15 values (all P < 0.001) (adjusted R 2 = 0.3857). Baseline GDF‐15 and changes in GDF‐15 at both 1 month and 8 months (log‐transformed) were associated with subsequent mortality and CV events. Each 20% increment in baseline GDF‐15 value was associated with a higher risk of mortality [adjusted hazard ratio (HR) 1.13, 95% confidence interval (CI) 1.08–1.18, P < 0.001], the combined endpoint of CV death or hospitalization for heart failure (adjusted HR 1.09, 95% CI 1.05–1.14, P < 0.001) and heart failure death (adjusted HR 1.16, 95% CI 1.05–1.28, P < 0.001). Changes in GDF‐15 were not influenced by assigned therapy (all P ‐values ≥ 0.1). Conclusion: In patients with ambulatory HFrEF, GDF‐15 is not modified by sacubitril/valsartan and is strongly associated with mortality and CV outcomes, suggesting that GDF‐15 is a marker of poor outcomes in these patients. Clinical Trial Registration:ClinicalTrials.gov Identifier NCT01035255.